The relationship between teachers’ self-efficacy, beliefs, and practice of differentiated instruction: A case study of a school in Kazakhstan - Kurmanova, Aliya (Nazarbayev University Graduate School of Education, 2019)
This explanatory sequential mixed methods instrumental case study explored the connection between teachers’ self-efficacy, beliefs and practice of differentiated instruction in one school in Kazakhstan. In response to new curriculum demands, teachers at the research site have begun using differentiated instruction. The purpose of the study was to identify teachers’ self-efficacy in regards to their willingness to use differentiated instruction in their classrooms, and their perception and practices of differentiated instruction. The quantitative component of this case study allowed the researcher to use a self-assessment survey to identify participants’ degree of perceived and differentiated instruction self-efficacy. Their perception and practice of differentiated instruction was qualitatively explored through semi-structured interviews, lesson observations and documents analysis. The study has revealed that most participants feel quite confident in their ability to perform new tasks and not allow challenges to discourage them. Also, the majority of participants showed high self-efficacy in their knowledge of differentiated instruction. However, findings showed that teachers’ high self-efficacy in differentiated instruction was not reflected in their practice. Furthermore, research showed that participants had varied perceptions of differentiated instruction. Some teachers understand it as a way to build a learning opportunity to meet the needs of their students. Others saw it as an abilitybased approach to meet the requirements of new curriculum. Overall teachers agreed that there was a connection between their confidence in performing new tasks and their willingness to employ differentiated instruction. The research findings can benefit teachers’ understanding of how self-efficacy can influence their readiness to use innovative teaching methods, including differentiated instruction. Also, the results of the study will be most beneficial to teachers as they can learn about their own practice reading this research. The study indicates the importance for school administration to encourage professional communities to help expand teachers’ perceptions of differentiated instruction.
Keywords: self-efficacy; beliefs; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; differentiated instruction; relationship; elf-efficacy